Forensic toxicology experience: Children poisoning cases in Riyadh, Saudi Arabia - Bandr Fakiha, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: This study aimed at analyzing the toxicological aspects of pediatric poisoning cases in Riyadh, Saudi Arabia. Child poisoning is a common cause of visits and admission to the emergency department, and it is essential in the identification of chemical causes of poisoning, particularly in children who are most vulnerable to poisonous substances such as drugs, chemicals, and pesticides, among other non-food substances. Methodology: The study adopted a cross-sectional descriptive research style, and secondary data from the Ministry of Health (MoH) Saudi Arabia were extracted between 2019 and 2021. The collected data on the demography of the patients, place of exposure, and whether the poisoning occurred accidentally or deliberately were analyzed descriptively using Microsoft Excel. Results and Discussion: This research established that male children are more prone to poisoning. Among them, children aged 1–5 were the most vulnerable group — 78,83 % of cases in 2019 and 81,26 % in 2020. Owing to chronic poisonings, more than 90% of the cases happened at home, and unintentional poisoning cases increased from 55.56% in 2019 to 84.49% in 2021, probably due to improved reporting. Non-accidental poisonings, in general, were not very frequent, but among the cases of juveniles, there were slightly more. Conclusion: The implications discussed here in the overview require developing better campaigns on preventing pediatric poisoning, improving the services offered by poison control centers, and improving the detection and treatment services provided by forensic toxicology.